A combined theoretical and experimental EXAFS study of the structure and dynamics of Au147 nanoparticles. Issue 18 (9th June 2016) - Duan, Zhiyao; Li, Yuanyuan; Timoshenko, Janis; Chill, Samuel T.; Anderson, Rachel M.; Yancey, David F.; Frenkel, Anatoly I.; Crooks, Richard M.; Henkelman, Graeme
Abstract : We demonstrated the capability of combined EXAFS and DFT calculations for characterizing the structural and thermal properties of Au147 clusters. Abstract : In this study, we present a framework for characterizing the structural and thermal properties of small nanoparticle catalysts by combining precise synthesis, extended X-ray absorption fine structure (EXAFS) spectroscopy, and density functional theory (DFT) calculations. We demonstrate the capability of this approach by characterizing the atomic structure and vibrational dynamics of Au147 . With the combination of EXAFS spectroscopy and DFT, the synthesized Au147 nanoparticles are determined to have an icosahedral structure. A decrease in the Einstein temperature of the Au147 particles compared to their bulk value was observed and interpreted in terms of softer vibration modes of surface bonds.